Optical spectroanalyzer with extended dynamic range for pharmacokinetic investigations of photosensitizers in biotissue - G. A. Meerovich; E. V. Akhlyustina; T. A. Savelieva; K. G. Linkov; V. B. Loschenov (Biomedical Photonics)
Currently, the most promising method for the study of pharmacokinetics of drugs with fluorescent properties is the spectral-fluorescent method. In this article, we propose an algorithm for expanding the dynamic range of the spectrum analyzer by automatically monitoring the maximum spectral density in the recorded fluorescence spectrum and automatically controlled changes in the accumulation time depending on this value, followed by compensation of the output signal with regard to this change, as well as hardware circuit solutions that allow this algorithm.Testing of LESA-01-"Biospeс" spectrum analyzer, upgraded using the proposed approach, was carried out on photosensitizer dispersions based on tetra-3-phenylthiophthalocyanine hydroxyaluminium of various concentrations (from 0.01 mg/l to 50 mg/l), approximately corresponding to the concentrations realized in the process of studying pharmacokinetics in calibration samples and tissues of experimental animals.The proposed solutions that implement the algorithm for recording fluorescence spectra with automatic change of accumulation time depending on the signal level, ensured a significant expansion of the dynamic range of the spectrum analyzer (up to 3.5 orders of magnitude) and improved accuracy in pharmacokinetic studies.